An Approach to Developing Cyanines with Upconverted Photosensitive Efficiency Enhancement for Highly Efficient NIR Tumor Phototheranostics. Issue 31 (12th September 2022) - Zhao, Xueze; He, Shan; Chi, Weijie; Liu, Xiaogang; Chen, Pengzhong; Sun, Wen; Du, Jianjun; Fan, Jiangli; Peng, Xiaojun
Abstract: Upconverted reactive oxygen species (ROS) photosensitization with one‐photon excitation mode is a promising tactic to elongate the excitation wavelengths of photosensitive dyes to near‐infrared (NIR) light region without the requirement of coherent high‐intensity light sources. However, the photosensitization efficiencies are still finite by the unilateral improvement of excited‐state intersystem crossing (ISC) via heavy‐atom‐effect, since the upconverted efficiency also plays a decisive role in upconverted photosensitization. Herein, a NIR light initiated one‐photon upconversion heavy‐atom‐free small molecule system is reported. The meso‐rotatable anthracene in pentamethine cyanine (Cy5) is demonstrated to enrich the populations in high vibrational–rotational energy levels and subsequently improve the hot‐band absorption (HBA) efficiency. Moreover, the spin–orbit charge transfer intersystem crossing (SOCT‐ISC) caused by electron donated anthracene can further amplify the triplet yield. Benefiting from the above two aspects, the 1 O2 generation significantly increases with over 2‐fold improved performance compared with heavy‐atom‐modified method under upconverted light excitation, which obtains efficient in vivo phototheranostic results and provides new opportunities for other applications such as photocatalysis and fine chemical synthesis. Abstract : A heavy‐atom‐free molecular design approach for achieving NIR upconverted photosensitization is reported. By modifying rotatable electron donating group at the meso position of Cy5, both the hot band absorption efficiency and intersystem crossing are improved. Moreover, the instructive design approach is also applicable in Cy5.5 system compounds, which provides new opportunities for NIR photosensitization applications.